Survival after Intensity Modulated Radiotherapy in Stage IIIB Cancer Cervix with or without Hydronephrosis - Youssif, Ayatallah; Abd Elzaher, Ahmed Refaat (Asian Pacific Journal of Cancer Care, 2025)
Background: Cervical cancer is the fourth most common cancer in women. There is lack of awareness and access to screening services in Egypt. Consequently, most cancers are diagnosed in advanced stages often with obstructive uropathy. Methods: This prospective phase II study included 46 cervical cancer patients with stage III B (as per pre-2018 FIGO staging) presented to the Radiation Oncology Department at South Egypt Cancer Institute from January 2019 to January 2024. Patients with or without hydronephrosis. Age group between 40 and 72 years, were included. Intensity modulated radiotherapy was delivered with concurrent chemoradiation to a dose of 45 Gy in 25 fractions over 5 weeks given to whole pelvis and in case of enlarged Para aortic or retroperitoneal lymph nodes, a boost of 9 Gy was given to these enlarged nodes. Fourty one patients received intracavitary brachytherapy. Results: The 5-year survival for patients who received radiotherapy alone was 31 % versus 86% for those who received chemoradiotherapy. The 3-year PFS was 88%. The 5- year survival was 30% versus 88% in those with and without obstructive uropathy respectively. Overall, after a mean time of 44.18+_ 7.48/44.0 (36-62) months, 76.1% of the studied patients were alive without any evidence of recurrence. Conclusions: IMRT allows to obtain a high rate of local control and survival in cancer cervix without obstructive uropathy. To achieve optimal results, it should be chosen in selected patients.